Signaling events driving Aspergillus fumigatus-induced eosinophil activation - Jasmin Adam; Lisa-Marie Graf; Stefanie Westermann; David Voehringer; Sven Krappmann (International Journal of Medical Microbiology)
Allergic bronchopulmonary aspergillosis is an incurable disease caused by the environmental mold Aspergillus fumigatus. This hypersensitivity pneumonia is characterized by an inflammatory type 2 immune response, accompanied by influx of eosinophils into the lung. To investigate the mode of action of eosinophils and the signaling events triggered by A. fumigatus, we used an in vitro coculture system of murine bone marrow-derived eosinophils confronted with conidia. Using small-molecule inhibitors, we identified signaling modules of eosinophils in the course of A. fumigatus confrontation. Eosinophils reduced fungal metabolic activity, but inhibition of relevant signaling modules did not affect this phenomenon upon eosinophil confrontation. A. fumigatus-induced secretion of Th2 cytokines and chemokines by eosinophils engaged proto-oncogene tyrosine-protein kinase Src, phosphatidylinositol 3-kinase, p38 mitogen-activated protein kinase as well as calcium cations and to some extent serine/threonine-protein kinase Akt and protein arginine deiminase 4. Src and PI3K kinases were also involved in A. fumigatus-mediated ROS production and regulation of eosinophils surface receptors. Especially Src and PI3K inhibitors prevented A. fumigatus-induced eosinophil activation. Taken together, identification of signaling cascades of eosinophils during their interaction with A. fumigatus provides relevant insights into the host-pathogen interaction in the context of ABPA to yield therapeutic perspectives.